Insights into the Mechanisms of Absence Seizure Generation Provided by EEG with Functional MRI - Carney, Patrick W.; Jackson, Graeme D. (Frontiers in Neurology, 2014)
Absence seizures are brief epileptic events characterized by loss of awareness with subtle motor features. They may be very frequent, and impact on attention, learning and memory. A number of pathophysiological models have been developed to explain the mechanism of absence seizure generation which rely heavily on observations from animal studies. Studying the structural and functional relationships between large-scale brain networks in humans is only practical with non-invasive whole brain techniques. EEG with functional MRI (EEG-fMRI) is one such technique that provides an opportunity to explore the interactions between brain structures involved in AS generation. A number of fMRI techniques including event-related analysis, time course analysis and functional connectivity have identified a common network of structures involved in AS seizures. This network comprises the thalamus, midline and lateral parietal cortex (the default mode network [DMN]), caudate nuclei and the reticular structures of the pons. The main component displaying an increase in BOLD signal relative to the resting state, in group studies, is the thalamus while the most consistent cortical change is reduced BOLD signal in the DMN. Time course analysis shows that, rather than some structures being activated or inactivated during AS, there appears to be increase in activity across components of the network preceding or following the electro-clinical onset of the seizure. The earliest change in BOLD signal occurs in the DMN, prior to the onset of epileptiform events. This region also shows altered functional connectivity in patients with absence seizures. Hence it appears that engagement of this network is central to absence seizures. In this review we will explore the insights EEG-fMRI studies into the mechanisms of AS and considers how the DMN is likely to be the major large scale brain network central to both seizure generation and the seizure manifestations.